Anti-inflammatory activity and identification of the Verbena litoralis Kunth crude extract constituents - Rachel de Lima; Juliana Calil Brondani; Rafaela Castro Dornelles; Cibele Lima Lhamas; Henrique Faccin; Carine Viana Silva; Sérgio Luiz Dalmora; Melânia Palermo Manfron (Universidade de São Paulo, 2020)
Verbena litoralis is a plant popularly known as "gervãozinho-do-campo" in Portuguese. It is traditionally used for stomach, liver and gallbladder problems, and as an anti-inflammatory and anthelmintic. The goal of this study was to determine the chemical composition of the crude extract obtained from the aerial parts of V. litoralis by Ultra High Performance Liquid chromatography coupled with Mass Spectrometry in Tandem (UHPLC-MS/MS); assess the anti-inflammatory activity of ethyl acetate fraction and of crude extract; and verify liver, kidney and pancreas damage. In this study, the chemical composition of the extract was identified via UHPLC/MS/MS, assessing the anti-inflammatory activity of the crude extract and the acetate fraction in an induction model of the granulomatous tissue, as well as given liver, kidney and pancreas damage markers. Chlorogenic acid, luteolin, caffeic acid, apigenin, p-coumaric acid, vanillic acid, ferulic acid and quercetin were quantified in the extract. After the seven-day treatment, the granuloma of the animals treated with the plant extract and fraction presented values very close to the positive control (nimesulide). The V. litoralis crude extract and ethyl acetate fraction show anti-inflammatory activity similar to the nimesulide without evidence of liver, kidney and pancreas damage, which attributes the plant's pharmacological action to the flavonoids found.